Ovicidal effect of four plant extracts on the eggs of Corcyra cephalonica (Stainton) - P, Zambare S; P, Kangade Y; T, Sharma C; H, Mali K (International Multidisciplinary Research Journal, 2012)
Extracts from Four plants, leaves of Argemone mexicana Euphorbia tirucalli, Nerium oleander and cotyledons of Semecarpus ancardium tested against eggs of Corcyra cephalonica. In contact toxicity test of different concentration of plant extract i.e 1ml, 2ml, 3ml and 4ml were applied on the freshly laid eggs. The inhibition of egg hatching increased with increased in concentration of plant extracts. It was observed that at 4 ml concentration of chloroform extract of Argemone mexicana exhibited 60.02 % ovicidal action whereas at the same concentration cotyledons of Semecarpus anacardium, phylloclade of Euphorbia tirucalli, Nerium oleander exhibit 45.72%, 34.64%, 39.83% respectively.